Changes in urinary potassium excretion in patients with chronic kidney disease - Ueda, Yuichiro (Kidney Res Clin Pract, 2016)
BACKGROUND: Hyperkalemia is one of the more serious complications of chronic kidney disease (CKD), and the cause of potassium retention is a reduction in urinary potassium excretion. However, few studies have examined the extent of the decrease of urinary potassium excretion in detail with respect to decreased renal function. METHODS: Nine hundred eighty-nine patients with CKD (CKD stages G1 and G2 combined: 135; G3a: 107; G3b: 170; G4: 289; and G5: 288) were evaluated retrospectively. Values for urinary potassium excretion were compared between CKD stages, and the associations between urinary potassium excretion and clinical parameters, including diabetes mellitus status and use of renin–angiotensin–aldosterone system inhibitors, were analyzed using a multivariable linear regression analysis. RESULTS: Urinary potassium excretion gradually decreased with worsening of CKD (G5: 24.8 ± 0.8 mEq/d, P < 0.001 vs. earlier CKD stages). In contrast, the value of fractional excretion of potassium at CKD G5 was significantly higher than that at the other stages (30.63 ± 0.93%, P < 0.001). Multivariable linear regression analysis revealed that urinary potassium excretion was independently associated with urinary sodium excretion (standardized coefficient, 0.499), the estimated glomerular filtration rate (0.281), and serum chloride concentration (–0.086). CONCLUSION: This study demonstrated that urinary potassium excretion decreased with reductions in renal function. Furthermore, urinary potassium excretion was mainly affected by urinary sodium excretion and estimated glomerular filtration rate in patients with CKD, whereas the presence of diabetes mellitus and use of renin–angiotensin–aldosterone system inhibitors were not associated with urinary potassium excretion in this study.